2014
DOI: 10.1007/s10067-014-2609-z
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the EuroQol EQ-5D and Hospital Anxiety and Depression Scale (HADS) in rheumatoid arthritis patients receiving tocilizumab

Abstract: The aim of this study was to assess the responsiveness to change of the quality of life evaluated by the EuroQol Five Dimensions Questionnaire (EQ-5D) and Hospital Anxiety and Depression Scale (HADS) after biological treatment in a population of rheumatoid arthritis patients. A cohort of patients with RA (n = 29) treated with tocilizumab (TCZ) were analyzed in the study. The inclusion criteria were patients aged between 18 and 65 years, fulfilling American College of Rheumatology 1987 criteria for RA. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…Tocilizumab yields its anti-inflammatory effects via an IL-6 receptor blockade, which involves inhibiting the IL-6 ligand from binding to IL-6R and sIL-6R [145,146]. Preliminary evidence has suggested that tocilizumab may have variable effects on improving mood symptoms in patients with RA [147,148]. In addition, there are other anti-IL-6R compounds that are currently pending clinical approval.…”
Section: Adjunctive Anti-inflammatory Treatment For Mddmentioning
confidence: 98%
“…Tocilizumab yields its anti-inflammatory effects via an IL-6 receptor blockade, which involves inhibiting the IL-6 ligand from binding to IL-6R and sIL-6R [145,146]. Preliminary evidence has suggested that tocilizumab may have variable effects on improving mood symptoms in patients with RA [147,148]. In addition, there are other anti-IL-6R compounds that are currently pending clinical approval.…”
Section: Adjunctive Anti-inflammatory Treatment For Mddmentioning
confidence: 98%
“…The use of tocilizumab, a humanized antibody against IL-6 receptor, or sirukumab, a humanized antibody against IL-6 have been proposed as novel antidepressant therapeutics (Traki et al, 2014;Hsu et al, 2015). Two ongoing clinical trials will examine the antidepressant effects of tocilizumab and sirukumab among patients with treatment-refractory major depression (www.clinicaltrials.gov).…”
Section: Anti-inflammatory Therapeuticsmentioning
confidence: 99%
“…Background: Many patients with rheumatoid arthritis (RA) experience anxiety and depression, with higher presence of these disorders in those with poorer outcome [1]. Previous experiences found relationships with psychological status and disease activity in patients with active disease [2,3]. Further evidences are needed to asses the impact on residual RA activity during treatment.…”
Section: Discussionmentioning
confidence: 99%